Business Sustainability and Challenges of Climate Change in Nigerian Indigenous Automobile Companies. A case study of Innoson Motors Ltd, Nnewi, Nigeria - Marcus Garvey Orji; Romanus Nduji (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
Business sustainability is one of the most important challenges of our time. Companies are integrating ideas of sustainability in their marketing, corporate communications, and in all their actions. It is for this reason that this study examined Business sustainability and challenges of climate change in Nigerian Indigenous Automobile Companies with particular emphasis on Innoson Motors Nnewi, Nigeria. The study is a survey research and data were collected from both primary and secondary sources. The target population of the study was 258 employees of the company, and the sample size of 157 was obtained using Taro Yamani. The statistical tool used for data analysis was mean, standard deviation, correlation and multiple regression analysis. The findings revealed that there is a positive relationship between sustainable profit, organizational workers, business opportunities and climate change in Innoson Motors, Nnewi Nigeria. The study therefore recommended that Companies should deploy smart technologies, Invest in new, more environmentally conscious technologies such as green data centre as source of cost reduction as well as competitive advantage; also for there to be a meaningful movement towards absolute emission reduction, companies must test the concept of a trade-off between economic performance and environmental responsibility.